Radial dispersion of red blood cells in blood flowing through glass capillaries: the role of hematocrit and geometry - Lima, Rui A. (2008)
The flow properties of blood in the microcirculation depend strongly on the hematocrit (Hct), microvessel geometry, and cell properties. Previous in vitro studies have measured the radial displacement of red blood cells (RBCs) at concentrated suspensions using conventional microscopes. However, to measure the RBCs motion they used transparent suspensions of ghost red cells, which may have different physical properties than normal RBCs. The present study introduces a new approach (confocal micro-PTV) to measure the motion of labeled RBCs flowing in concentrated suspensions of normal RBCs. The ability of confocal systems to obtain thin infocus planes allowed us to measure the radial position of individual RBCs accurately and to consequently measure the interaction between multiple labeled RBCs. All the measurements were performed in the center plane of both 50 mm and 100 mm glass capillaries at Reynolds numbers (Re) from 0.003 to 0.005 using Hcts from 2 to 35%. To quantify the motion and interaction of multiple RBCs, we used the RBC radial dispersion (Dyy). Our results clearly demonstrate that Dyy strongly depends on the Hct. The RBCs exhibited higher Dyy at radial positions between 0.4 R and 0.8 R and lower Dyy at locations adjacent to the wall (0.8 R–1 R) and around the middle of the capillary (0 R–0.2 R). The present work also demonstrates that Dyy tends to decrease with a decrease in the diameter. The information provided by this study not only complements previous investigations on microhemorheology of both dilute and concentrated suspensions of RBCs, but also shows the influence of both Hct and geometry on the radial dispersion of RBCs. This information is important for a better understanding of blood mass transport mechanisms under both physiological and pathological conditions.